ANALISIS MISKONSEPSI MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL PADA BUKU PELAJARAN MATEMATIKA UNTUK SMP/MTs KELAS VIII EDISI REVISI 2017 - Fery Sinabutar; Julia Agnesia Harianja; Goodwill Lumbantobing; Inna Umi Fadillah; Wan Saskia Putri; Wingston Leonard Sihombing (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze misconceptions found in the material of Two-Variable Linear Equation Systems (SPLDV) in the 2017 revised edition of Mathematics textbooks for grade VIII of SMP/MTs. The method used is content analysis with a qualitative approach to identify errors in material presentation that potentially cause misconceptions among students. The results reveal errors related to facts, concepts, principles, and operations in the textbook that may affect students’ understanding of SPLDV. These findings are expected to provide input for textbook developers and teachers to improve the quality of mathematics learning